Boganmeldelser - Garde, Peter; Bech, Charlotte Mathiesen; Larsson, Paul; Langsted, Lars Bo; Elholm, Thomas; Klette, Hans; Flyghed, Janne; Kruize, Peter (Nordisk Tidsskrift for Kriminalvidenskab, 2002)
Book reviews